2007
DOI: 10.1093/bja/ael316
|View full text |Cite
|
Sign up to set email alerts
|

Blind placements of peripherally inserted antecubital central catheters: initial catheter tip position in relation to carina

Abstract: Right antecubital PICCs are more likely to be placed in the central location in relation to the carina. PICCs inserted through the left antecubital veins need to be pushed further down to aim for a central location. Inter-observer variability in identifying the tip of PICCs is least with the introduction of digital imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 20 publications
3
48
1
Order By: Relevance
“…found that though a central location was the most common tip position for right-sided PICCs, the brachiocephalic vein (ipsilateral) was the commonest location for left-sided ones. [34] In contrast, our study showed that acceptable positioning of catheter tips was not statistically different for right- and left-sided catheters.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…found that though a central location was the most common tip position for right-sided PICCs, the brachiocephalic vein (ipsilateral) was the commonest location for left-sided ones. [34] In contrast, our study showed that acceptable positioning of catheter tips was not statistically different for right- and left-sided catheters.…”
Section: Discussioncontrasting
confidence: 75%
“…reported 11% of PICC entering the IJV. [34] An 18% incidence has been reported in two different studies by Ragasa and coworkers and Burgess and colleagues. [2235] The same incidence quoted in pediatric population ranges from 14 to 37%.…”
Section: Discussionmentioning
confidence: 99%
“…That incidence of malposition is similar to the incidences reported in other studies. 32,38,39 Malpositioned tips were located in the upper or middle third of the SVC, the ipsilateral subclavian vein, the right atrium, the ipsilateral internal jugular vein, and the axillary vein. In 1 case, the tip was coiled in the SVC (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The tip locations and incidences are similar to those reported in other studies. 32,38,39 These reports show that about 58% of malpositions were corrected with catheter exchange, and 83% were corrected by repositioning the catheter in the interventional radiology division under imaging guidance. 32,38,39 In this study, we demonstrated a modification of PICC insertion: taking the chest radiograph earlier, which makes it easier to correct malpositions at the bedside, with high success rates and without catheter exchange.…”
Section: Discussionmentioning
confidence: 99%
“…PICCs have recently become popular because they perform well in overcoming problems associated with limited peripheral access and frequent venipuncture in patients undergoing long-term therapy. In particular, blind PICCs -those done without an imaging assistant -have been used by many institutions for easy, cost effective, and safe placement [6,7]. For burn patients, PICCs were compared with CVCs for both use and safety issues, and PICCs performed well in relation to CR-BSI [8].…”
Section: Introductionmentioning
confidence: 99%